Temporary anions of the dielectric gas C3F7CN and their decay channels - Ranković, M; Kumar T P, Ragesh; Nag, P; Kočišek, J; Fedor, J (The Journal of chemical physics, 2020)
We probe the transient anion states (resonances) in the dielectric gas C4F7N by the electron energy loss spectroscopy and the dissociative electron attachment spectroscopy. The vibrationally inelastic electron scattering leads to two excitation types. The first is the excitation of specific vibrational modes that are assigned with the help of an infrared spectrum of this molecule and quantum chemistry calculations. In the second type of vibrational excitation, the excess energy is randomized via internal vibrational redistribution in the temporary anion, and the electrons are emitted statistically. The electron attachment proceeds in three different regimes. The first is the formation of the parent C4F7N- anion at energies close to 0 eV. The second is a statistical evaporation of the F-atom, leading to the defluorinated anion C4F6N-. Finally, the third is dissociative electron attachment proceeding via the formation of several resonances and leading to a number of fragments. The present data explain the puzzling recent results of the pulsed-Townsend experiments with this gas.